MODEL PROBLEM BASED LEARNING ( PBL) BERBASIS POTENSIS LOKAL TANAMAN NIPAH SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR IPAS MURID SEKOLAH DASAR - Taribaba, Yemima; Wabiser, Yan Dirk; Suwita; Yektiningtyas, Wigati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Natural and social sciences are fields of study that examine living organisms, natural phenomena, and their roles in life. Integrated Natural and Social Sciences (IPAS) learning in elementary schools emphasizes students’ active involvement through contextual and meaningful learning experiences. However, in practice, the learning motivation of students at SD Negeri Inpres Waroki is still relatively low because the learning process tends to be conventional and less connected to local potential. In addition, the use of nipa palm plants as learning media in IPAS learning remains limited. This study aims to describe the implementation and analyze the impact of the Problem Based Learning (PBL) model based on the local potential of nipa palm plants as an effort to improve students’ motivation in learning IPAS at SD Negeri Inpres Waroki.This study employed a qualitative approach with a descriptive research design. The research subjects were fourth-grade students and teachers at SD Negeri Inpres Waroki. Data collection techniques included observation, interviews, and documentation. Data were analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the nipa palm plant-based PBL model was able to improve students’ learning motivation at SD Negeri Inpres Waroki, as indicated by increased activeness, curiosity, cooperation, and student engagement in the learning process. Furthermore, learning became more meaningful because it was connected to the students’ surrounding. Therefore, the PBL model based on the local potential of nipa palm plants is effective in improving students’ motivation in learning IPAS at SD Negeri Inpres Waroki.